A Spoke in the Wheel: Enhancing Chaplaincy Documentation in Interdisciplinary Care Settings - Fudge, Eric J. (Journal of pastoral care & counseling, 2021)
Chaplaincy is a spoke in the wheel of interdisciplinary care that uses its disciplines to better the patient’s medical condition. Therefore, chaplains ought to consider how their emotional and spiritual support helps interdisciplinary teams treat patients’ illnesses/injuries. This essay explores how chaplains can contribute more effectively to interdisciplinary care by keeping their patients’ condition in focus throughout their spiritual assessments and using models that are familiar to the medical team.